21st Century Character Education for Indonesian Children through Sport Science - I Gede Suwiwa; I Made Sutajaya; I Gusti Putu Sudiarta; Wahjoedi Wahjoedi; I Ketut Iwan Swadesi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aimed to examine 21st-century character education for Indonesian children through Sports Science which was implemented in the form of integration of physical education and character education in early childhood, especially through sports activities such as; pencak silat (martial arts), dance, outbound, and swimming. This study used a literature research method by adapting a literature study research model proposed by Mirshad (2014) which was carried out through four research steps, namely; 1) recording of all findings 2) integration of all findings 3) analysis of all findings, 4) criticism and collaboration. The instrument used was a data card where data were recorded by paraphrasing, quoting, and synoptic. Document Analysis was used for data analysis that focused more on analyzing factual content and media features. This study found several characters that appeared in four activities, namely; 1) pencak silat (martial arts) could increase the character values of piety, not giving up easily, responsibility, discipline, and self-confidence; 2) the art of dance fostered the character of honesty, cooperation, independence, self-confidence, piety, and discipline; and 3) outbound created the character of leadership, cooperation, and self-confidence; 4) swimming could increase the character values of courage, self-confidence, creativity, adaptation, and sensitivity. This character could grow and develop from each activity created in the four activities. It was recommended for parents to provide opportunities for their children to participate in sports activities such as; pencak silat (martial arts), dance, outbound, and swimming because these activities had been proven to increase positive character, where these activities were an integration of physical education as an academic discipline based on sports science.